The Influence of Brand Image and Patient Experience on Patient Decision to Do Medical Check-Up in Siloam Sentosa Hospital and Consumer Motivation as an Intervening Variable - Febridayanti Nur Fitrianisa; Wahyu Dian Purwati; Idrus Jus’at (Lembaga Pengembangan Kinerja Dosen, 2025)
Siloam Sentosa Hospital always tries to provide a service that is appropriate to the expectations based on feedback from SOFAS and MCU Siloam Sentosa Hospital revenue has problem and doubtfull from patien to recomended MCU Service to acquintance. The Goals is research corelation and interaction between of Brand Image, Patient Experience, patient decision do medical check up and motivation consumer in Siloam Sentosa Hospital in 2022. Using categorical research with analytical method of study (explanatory student) using the design of cross-sectional research.. From Correlation test the result is > 0,5, it shows that inpendent variables giving the connection correlation. The result of Anova test theres siginificant relation simulataneously from Brand Image, Patient Experience and Consument Motivation as intervening variabel to decision patient do MCU. Dari hasil uji t maka disimpulkan variabel dependen dan inpenden memiliki hasil yang signifikan Hasil tersebut menunjukkan bahwa Brand image, Patient Experience, dan Motivasi konsumen sebagai variabel intervening memiliki pengaruh positif dan signifikan terhadap keputusan pasien melakukan MCU di Rumah Sakit Siloam Sentosa. The result from T test, concluded dependent and independent variable has significant result. It shows Brand Image, Patient Experience and Consument Motivation as intervening variable have a positive influence and significant to patient decision do MCU in Siloam Sentosa Hospital.